Interleukin 10 Polymorphisms as Risk Factors for Progression to Chagas Disease Cardiomyopathy: A Case-Control Study and Meta-Analysis - Grijalva, Alicia; Gallo Vaulet, Lucia; Agüero, Roberto Nicolas; Toledano, Analia; Risso, Marikena Guadalupe; Quarroz Braghini, Juan; Sosa, David; Ruybal, Paula; Repetto, Silvia; Alba Soto, Catalina Dirney (Frontiers in Immunology, 2022)
Background Chagas disease is a lifelong infection caused by the protozoa Trypanosoma cruzi endemic in Latin-America and emergent worldwide. Decades after primary infection, 20-30% of infected people develop chronic Chagas cardiomyopathy (CCC) while the others remain asymptomatic. CCC pathogenesis is complex but associated with sustained pro-inflammatory response leading to tissue damage. Hence, levels of IL-10 could have a determinant role in CCC etiology. Studies with Latin-American populations have addressed the association of genetic variants of IL-10 and the risk of developing CCC with inconsistent results. We carried out a case control study to explore the association between IL-10-1082G>A (rs18008969), -819C>T (rs1800871), -592A>C (rs1800872) polymorphisms and CCC in a population attending a hospital in Buenos Aires Argentina. Next, a systematic review of the literature and a meta-analysis were conducted combining present and previous studies to further study this association. Methods Our case control study included 122 individuals with chronic T. cruzi infection including 64 patients with any degree of CCC and 58 asymptomatic individuals. Genotyping of IL-10 -1082G>A, -819C>T, -592A>C polymorphisms was performed by capillary sequencing of the region spanning the three polymorphic sites and univariate and multivariate statistical analysis was undertaken. Databases in English, Spanish and Portuguese language were searched for papers related to these polymorphisms and Chagas disease up to December 2021. A metanalysis of the selected literature and our study was performed based on the random effect model. Results In our cohort, we found a significant association between TT genotype of -819 rs1800871 and AA genotype of -592 rs1800872 with CCC under the codominant (OR=5.00; 95%CI=1.12-23.87 P=0,04) and the recessive models (OR=5.37; 95%CI=1.12-25.68; P=0,03). Of the genotypes conformed by the three polymorphic positions, the homozygous genotype ATA was significantly associated with increased risk of CCC. The results of the meta-analysis of 754 cases and 385 controls showed that the TT genotype of -819C>T was associated with increased CCC risk according to the dominant model (OR=1.13; 95% CI=1.02–1.25; P=0,03). Conclusion The genotype TT at -819 rs1800871 contributes to the genetic susceptibility to CCC making this polymorphism a suitable candidate to be included in a panel of predictive biomarkers of disease progression.